ASPEK PRASEJARAH DI WILAYAH KABUPATEN TABALONG PROVINSI KALIMANTAN SELATAN - E.A. Kosasih (Berkala Arkeologi, 1998)
To further trace the archaeological potential that exists in the South Kalimantan region - especially in Tabalong Regency - the results of prehistoric research (and traditions) that have been carried out so far by the Banjarmasin Archeology Center in collaboration with the National Archaeological Research Center will be presented. The results of this research need to be disclosed, to better understand the archaeological potential in the Tabalong Regency area.